Deadpool corps (2010), volume 1 ebook Pool-pocalypse now. - Various, Marvel (Deadpool Corps (2010), 2024)
Collects Deadpool Corps #1-6. Deadpool in spaaaaace! When the universe is in peril, there’s only one hero who can protect us: Deadpool! (Wait, that can’t be right…) The consciousness-sapping cosmic entity called the Awareness has wiped out the free will of millions of planets — and it will take the combined might, cunning and unbridled insanity of the Deadpool Corps to stop it from destroying the galaxy! Handpicked from the cream of the alternate-universe crop, Lady Deadpool, Kid Deadpool, Dogpool and Zombie Headpool join the original Merc with a Mouth on an incredible interstellar adventure. If they can keep the in-fighting, vicious swordplay and binge drinking to a minimum, this crew of crazies just might just stand a chance.